Pendekatan Komunikasi Islam pada Nilai Mauizah Hasanah: (Telaah Konsep dan Aplikasi Dalam Kehidupan) - Junaidi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
Many of Islamic concepts are not implemented in daily life. This is due to the way the delivery of religious messages is still not quite right, God says Q. An-Nahl, 125.